(untitled) (Bangladesh Journal of Neuroscience, 2014)
Background: Analgesic drugs may produce toxic effect on the cochlear system depending on the dose, duration or concomitant renal failure. Objective: Our aim was to find out the relationship between analgesic use and hearing loss. Methods: This was a cross sectional study done combindly between E.N.T. and Neurology department of Bangladesh Medical college among the patients complaining of hearing loss of different degree. One hundred and forty four patients of both sexes having sensory-neural type of hearing loss were included in this study. Results: Out of 944 patients, eighty eight patients were taking tab. Diclofenac (61.11%), thirty six patients were taking Naproxen(25%), and twelve were taking Paracetamol (8.33%) eight were taking Ibuprophen(5.55%). Eighty eight patients were taking the drugs more than two years (61%). All patients were taking analgesic 3-4 times per week. Intensity of damage was severe in 52.77%; moderate damage was evident in 30.55% cases and mild damage found in 16.66% cases. Severity of damage was moderate to severe in most cases of Diclofenac. Conclusion: Analgesic drugs may have toxic effect on hearing. Bangladesh Journal of Neuroscience 2011; Vol. 27 (2) : 74-77 DOI: http://dx.doi.org/10.3329/bjn.v27i2.17572